The productivity effects of profit sharing, employee ownership, stock option and team incentive plans: Evidence from korean panel data - Takao Kato; Ju Ho Lee; Jang-soo Ryu (Institute for the Study of Labor (IZA), 2010)
We report the first results for Korean firms on the incidence, diffusion, scope and effects of diverse employee financial participation schemes, such as Profit Sharing Plans (PSPs), Employee Stock Ownership Plans (ESOPs), Stock Option Plans (SOPs) and Team Incentive Plans (TIPs). In do doing, we assemble important new panel data by merging data from a survey of all Korean firms listed on Korean Stock Exchange which enjoys an unusually high response rate of 60 percent with accounting data from their corporate proxy statements. Our estimated fixed effect models of production functions reveal consistently that the introduction of a PSP or a TIP will lead to a significant increase in productivity (about 10 percent) whereas no such evidence found for ESOPs or SOPs. We also find that the productivity payoff appears to be more long-lasting for PSPs than for TIPs. Finally, our fixed-effect estimates suggest that PSPs and TIPs tend to be substitutes rather than complements in their productivity effects.
urn:nbn:de:101:1-201009302480
Keywords: M52; J33; J24; J53; O53; 330; profit sharing; employee stock ownership; team incentive; stock option; productivity; Korea